2015
DOI: 10.1016/j.arr.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy in the ageing patient: The impact of age per se (A review)

Abstract: A literature search was carried out to review the influence of 'ageing' on pharmacotherapeutic decision-making, specifically how 'age' is defined and considered in the utilisation of medication. Embase, Medline, International Pharmaceutical Abstracts, and Google scholar were canvassed in a three-tiered search according to pre-established inclusion criteria. In tier 1, a total of 22 studies were identified highlighting the underutilisation of medication in elderly patients, with a particular focus on warfarin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 152 publications
(214 reference statements)
0
17
0
Order By: Relevance
“…Articles meeting the criteria were segmented into general adult and older adult populations based on the age range of the sample. Because the definition of the term "el-derly" is not always agreed, [6] this review has used the term "older adults" which refers to populations over the age of 50 years, as a subpopulation of the general adult population. The articles regarding general adult populations were grouped into five geographical regions.…”
Section: Methodsmentioning
confidence: 99%
“…Articles meeting the criteria were segmented into general adult and older adult populations based on the age range of the sample. Because the definition of the term "el-derly" is not always agreed, [6] this review has used the term "older adults" which refers to populations over the age of 50 years, as a subpopulation of the general adult population. The articles regarding general adult populations were grouped into five geographical regions.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 It is apparent that, despite acknowledging the inter-individual variability of older patients, a degree of ageism appears to exist among health professionals caring for older patients. [4][5][6][7] Singh and Bajorek observed that inappropriate prescribing (both over-treatment and under-treatment) is often detected in older patients, increasing the potential for adverse clinical outcomes. 8 Indeed, age-bias has been identified in the under-treatment of angina, rheumatoid arthritis, and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…8 Indeed, age-bias has been identified in the under-treatment of angina, rheumatoid arthritis, and hypertension. 5 It is reported that age-based decision-making in the use of high risk medications i.e. anticoagulants, may 'skew' a health care professionals risk-benefit assessment, resulting in potential patient harm such as stroke or even death.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations